The Typology of Motion Events : an Empirical Study of Chinese Dialects. (Empirical Approaches to Language Typology EALT., 2013)
This comprehensive study concentrates particularly on the use of a closed set of motion verbs in five of the major dialects, including Mandarin, Wú, Hakka, M?n and Cantonese. The author shows that these dialects form a continuum with some exhibiting more characteristics of a verb-framed language than the others. The phenomenon reflects the various stages of typological transformation and grammaticalization that the dialects have undergone.